DIGITIZATION OF HISTORICAL INFORMATION AT THE NATIONAL ARCHIVES OF ZAMBIA: CRITICAL STRATEGIC REVIEW PPT - Hamooya, Chrispin (My University, 2012)
Archives administration in Zambia is the mandate of the National Archives of Zambia (NAZ) of the Ministry of Home Affairs. This mandate is derived from the National Archives Act Chapter 175 of the Laws of Zambia, 1995 edition which provides for the preservation, custody, control and disposal of public archives including public records in Zambia.
Keywords: DIGITIZATION OF HISTORICAL INFORMATION AT THE NATIONAL ARCHIVES OF ZAMBIA: CRITICAL STRATEGIC REVIEW